New Weighted Hermite–Hadamard Type Inequalities for Differentiable h-Convex and Quasi h-Convex Mappings - Muhammad Amer Latif (Journal of Mathematics)
In this paper, new weighted Hermite–Hadamard type inequalities for differentiable h-convex and quasi h-convex functions are proved. These results generalize many results proved in earlier works for these classes of functions. Applications of some of our results to s˘-divergence and to statistics are given.